2019
DOI: 10.1111/cid.12779
|View full text |Cite
|
Sign up to set email alerts
|

A study on the prevalence of dental anxiety, pain perception, and their interrelationship in Chinese patients with oral implant surgery

Abstract: Background Accumulating evidence has revealed that dental anxiety (DA) is associated with pain and patient satisfaction related to dental procedures. However, relevant reports are limited and inconsistent in oral implant patients. Purpose The purpose of this study was to investigate the prevalence of dental anxiety, pain perception, and analyze their interrelationship in Chinese patients with oral implant surgery. Materials and Methods A cross‐sectional study was performed according to the strengthening the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
2
12
0
1
Order By: Relevance
“…Zhang et al, who assessed the dental anxiety and pain perception in patients with oral implant surgery, reported a prevalence of 66.6% and 11.9% moderate and high preoperative dental anxiety, respectively. The results of this study indicated that dental anxiety might increase pain perceptions of the patients during oral implant surgery (15). Muglali and Komerik investigated factors that may be linked with the anxiety of patients having minor oral surgery procedures (4).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al, who assessed the dental anxiety and pain perception in patients with oral implant surgery, reported a prevalence of 66.6% and 11.9% moderate and high preoperative dental anxiety, respectively. The results of this study indicated that dental anxiety might increase pain perceptions of the patients during oral implant surgery (15). Muglali and Komerik investigated factors that may be linked with the anxiety of patients having minor oral surgery procedures (4).…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria were as follows: (1) missing teeth; (2) in need of dental implant placement or bone augmentation procedures, or both; (3) older than 18 years; (4) with basic communication, reading and writing skills; and (5) willingness to sign an informed consent form. Exclusion criteria were: (1) patients receiving second-stage surgeries; (2) previously augmented sites; (3) sites with previous implant failure; (4) relative contraindications to dental implant therapy; (5) systematic diseases and psychological or medical disorders that might influence pain threshold; (6) use of pain medication within 1 year 8 ; (7) acute intraoral pain (periodontal or endodontic pain); and (8) acute infections in which oral sensitivity was affected.…”
Section: Methodsmentioning
confidence: 99%
“…In implant dentistry, patient-reported outcome measures (PROMs) such as patient anticipation of treatment outcomes,6 quality of life7 and discomfort due to dental implant surgery8 have received increasing research interest. With an understanding of PROMs, clinicians can ensure patients’ own perception of need, involve patient preference in clinical decision-making, and improve clinician–patient trust and subsequent patient oral hygiene maintenance 9–11.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study that assessed the association between anxiety and pain perception during dental implant surgery found that dental anxiety can increase patients' pain perception during oral implant surgery. 39 The presence of chronic pain or temporomandibular joint dysfunction was also not evaluated, a variable that could affect surgical discomfort.…”
Section: Total Of Included Individuals N=196mentioning
confidence: 99%